(untitled) (The Review of Diabetic Studies, 2025)
A pre-experimental research study aimed Impact of Mindfulness-Based Stress Reduction (MBSR) on Reducing Test Anxiety and Improving Academic Performance among high school students at Agrwal Vidhya Vihar School, Surat, Gujarat. A quantitative research approach with a one-group pre-test post-test design was employed. A total of 90 students were selected using a non-probability purposive sampling technique based on inclusion criteria. Data were collected using PSS-10 developed through literature review, expert validation, and pretesting. The educational intervention was delivered via a MBSR Program. The same questionnaire was administered as a pre-test and post-test with a 7-day interval to assess Anxiety score improvement. Statistical analysis using paired t-test showed a significant increase in post-test scores, indicating the module’s effectiveness. The chi-square test was used to find associations between post-test knowledge and demographic variables. Reliability of the tool was confirmed through test-retest (r = 0.84). The study concludes that structural educational interventions can effectively decreased anxiety and improved academic performance among high school students.